A critical investigation of PRME integration practices of the third cycle champion group. Issue 1 (March 2021) - Abdelgaffar, Hala A.
Abstract: The Principles of Responsible Management Education (PRME) are being increasingly mainstreamed into business and management education to embed ethics, social responsibility, and sustainability issues in educational and operational practices. The purpose of this study is to analyze the Sharing Information Progress (SIP) reports of 38 third cycle PRME Champion group to explore their level of engagement with the PRME agenda. A PRME Integration Framework (PIF) is used to map, categorize, and compare a multitude of responsible management education (RME) integration components corresponding to six principles of PRME. Each component is supported with scholarly work to validate using PIF as a metrics to monitor progress towards a consistent level of RME integration and enhance the quality of future SIPs. The Framework offers a practical guide for business schools on their transformational journey to RME adoption. It allows flexibility to add new categories in response to future triple bottom line and humanitarian challenges. The study examines achievements, gaps, and challenges and suggests means of improving the RME adoption process and SIP reporting mechanism. Overall, content analysis of the SIP reports of the PRME Champion group conveys exemplar creative, innovative, and verifiable practices, yet some of the SIP reports suffer inconsistency, vagueness, and limited details of the RME implementation process and strategies. Future multi-stakeholder networking, collaboration, and shared resources could help realizing the full potentials of PRME.